Imagination capacity in university students: aphantasia and its possible changes in personal development - Albuquerque Gouveia, Levi (Seven Editora, 2023)
This research is about Aphantasia, a condition in which the individual has his or her imagination capacity diminished or absent, and which can be acquired or congenital. This study aims to analyze the percentage of university individuals with aphantasia, within the three areas of knowledge (Human, Exact and Biological) and compare this percentage, within the university environment, with the percentage of aphantasia in the general population, which has already been estimated around 2% by researcher Adam Zeman. The study is of the cross-sectional observational type conducted with university students. Data collection will be performed from the Vividness of Visual Imagery Questionnaire (VVIQ), sent digitally and completed by participants by Google Forms. The collected data will be processed and analyzed in Microsoft Excel. As a result of the research it is expected to be able to analyze whether the percentage found of people with aphantasia in the university population is the same as that found in the general population. In a way, the expectation that is assumed is that the percentage of aphantasia found in the university environment is lower than the percentage found in the population, since the capacity for imagination and abstraction are useful instruments and facilitators of learning and construction of knowledge, both practical and abstract and that its absence can be a difficulty to enter the undergraduate course. From this, we will raise arguments, hypotheses and discussions about the data collected, addressing possible causes and consequences for it in the academic-educational environment and in personal development. DOI: https://doi.org/10.56238/tfisdwv1-057